2022
DOI: 10.3389/fpsyg.2022.927330
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nostalgia Proneness on Online Donation Willingness: The Mediating Effect of Consumer-Brand Relationship

Abstract: The rapid outbreak of COVID-19 wreaked havoc and brought a pause to the normal lives, and the labor market and human livelihoods were strongly negatively affected because of it. The emergence of groups that were unable to withstand various pressures has increased the appeal of donation behavior to a certain extent. Therefore, under the impetus of COVID-19 and digital background, online donation represented by Waterdrop financing has become popular. In the common difficult period, how to improve an individual’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…According to Boym (2008) , there are two types of nostalgia: “restorative nostalgia” and “reflective nostalgia.” “Reflective nostalgia” refers to reflecting on the remembered past for the purpose of the present and is often associated with establishing continuity. This kind of nostalgia is a positive experience that provides individuals with the opportunity to reflect on the past, which enhances self-worth, self-esteem, and social connectedness and promotes pro-social behavior ( Srivastava et al, 2022 ; Zhang and Tao, 2022 ). There may be a tendency for individuals to invoke nostalgia as a coping mechanism to deal with the social distance restrictions of COVID-19 and the resulting isolation and social disconnection.…”
Section: Discussionmentioning
confidence: 99%
“…According to Boym (2008) , there are two types of nostalgia: “restorative nostalgia” and “reflective nostalgia.” “Reflective nostalgia” refers to reflecting on the remembered past for the purpose of the present and is often associated with establishing continuity. This kind of nostalgia is a positive experience that provides individuals with the opportunity to reflect on the past, which enhances self-worth, self-esteem, and social connectedness and promotes pro-social behavior ( Srivastava et al, 2022 ; Zhang and Tao, 2022 ). There may be a tendency for individuals to invoke nostalgia as a coping mechanism to deal with the social distance restrictions of COVID-19 and the resulting isolation and social disconnection.…”
Section: Discussionmentioning
confidence: 99%
“…Sargeant et al (2006) identified emotional and familiar utilities as key factors that influence charitable giving decisions, with emotional utility referring to the motivation to give to a charity derived from a desire for one’s own emotional benefit, and familiar utility referring to the motivation to give derived from a desire to benefit family members or significant others. A recent study on nostalgia and donation found that increased emotional and familiar utilities were associated with a greater intention to donate to charitable causes, even during challenging times such as the COVID-19 pandemic (Zhang & Tao, 2022). Although research on the relationship between music-evoked nostalgia and prosocial behavior is very limited, our study’s findings are in line with prior research on nostalgia and donation in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…, 2021; Maftei, 2020; Martin and Randal, 2008, 2009; Urandelger et al. , 2016; Zhang and Tao, 2022). Individuals are more likely to donate when they feel good about helping others (Prendergast and Maggie, 2013; Bock et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The tendency to donate is motivated by several intrinsic and extrinsic factors (Huang et al, 2021;Maftei, 2020;Randal, 2008, 2009;Urandelger et al, 2016;Zhang and Tao, 2022). Individuals are more likely to donate when they feel good about helping others (Prendergast and Maggie, 2013;Bock et al, 2018) when they believe they are making a difference, when they have social motivations, when they think it will make others feel better and when they believe it will provide them with a good reputation (Van Leeuwen and Wiepking, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation